Livestock Trypanosomosis In Uganda: Parasite Heterogeneity And Anaemia Status Of Naturally Infected Cattle, Goats And Pigs - Biryomumaisho, Savino; Rwakishaya, Eli-Katunguka; Melville, Sara Elizabeth; Cailleau, Aurélie; Lubega, George William (Parasitology research, 2013)
The prevalence and pathogenic effects of trypanosomosis were determined in cattle, goats and pigs reared in Kasese, Jinja and Rakai districts, Uganda; presence of trypanosomes was detected by buffy coat technique (BCT). The overall prevalence of trypanosomosis in cattle was 7.6 % (144/1,891), 0.7 % in goats (4/573) and 2.3 % in pigs (9/386). Internal transcribed spacer 1 (ITS1) of ribosomal DNA polymerase chain reaction was utilised to identify trypanosomes to species level and revealed infections in 108 of the 144 trypanosome-positive cattle while all infected goats and pigs gave amplicons. Trypanosoma vivax was the most prevalent trypanosome species in cattle in single and mixed infections compared to infections involving Trypanosoma congolense and Trypanosoma brucei; in pigs, eight were mixed infections with one single T. vivax infection. No predominant trypanosome species was detected in goats. Anaemia, the main trypanosomosis pathological feature, was investigated by determining packed cell volume (PCV). Mean PCV values by t test in infected individuals were significantly lower than non-infected individuals (P < 0.05) for all animal species. However, the proportion of anaemic animals was not significantly different in infected and non-infected individuals. In addition, the percent of infected animals by Fisher’s exact test depended on district of origin and species but not sex. These findings show that trypanosomosis is a major cause of anaemia in livestock in endemic areas. Cattle were the major animal species affected by trypanosomosis; similar genotypes of trypanosomes were detected in the three animal species. BCT was more effective than ITS1 rDNA detecting trypanosomes in naturally infected cattle.
Keywords: Trypanosoma; Pack Cell Volume; Trypanosome Species; Trypanosoma Congolense ;Trypanosoma Vivax